Regional analysis and stage-specific incidence of breast cancer in Kazakhstan: A comprehensive study - Nurbek Igissin; Assem Toguzbayeva; Zhansaya Telmanova; Gulnur Igissinova; Dulat Turebayev; Dariyana Kulmirzayeva; Nariman Syzdykov; Rustem Moldagali; Daulet Baibosynov; Zarina Bilyalova (Clinical Epidemiology and Global Health)
Background: Breast cancer is the most prevalent oncological pathology in Kazakhstan, ranking among the top three causes of cancer-related deaths in women. The objective of this study is to analyze the incidence of breast cancer, considering factors such as stage, age, sex, and morphological verification in the regional context in Kazakhstan. Methods: The retrospective study employed descriptive and analytical oncoepidemiological methods. Breast cancer incidence data (2005–2019) were obtained from the Unified Nationwide Electronic Health System (ICD-10 code C50). Demographic data came from the Bureau of National Statistics. Statistical analyses included age-standardized, crude, and age-specific incidence rates, with trend analyses performed using linear regression and the Joinpoint Regression Program to assess average percentage change over time. Results: The analysis of breast cancer incidence in Kazakhstan shows significant regional variations and an overall upward trend. Nationally, the age-standardized incidence rate is 40.9 per 100,000, with an annual increase of +1.96 %. Early-stage (I-II) breast cancer incidence is rising, particularly in Pavlodar, North Kazakhstan, and Almaty City. In contrast, advanced-stage (III-IV) incidence has generally declined, except in regions like Kostanay, North Kazakhstan, and Atyrau, where late-stage cases are increasing. High morphological verification rates across all regions ensure reliable and accurate diagnostic data. Conclusion: The study reveals a significant increase in early-stage breast cancer diagnoses in Kazakhstan, highlighting the effectiveness of the national screening program. However, regional disparities in late-stage cancer incidence suggest a need for targeted interventions and improved regional healthcare.